2011
DOI: 10.1097/aln.0b013e31822a22be
|View full text |Cite
|
Sign up to set email alerts
|

High Oxygen Partial Pressure Decreases Anemia-induced Heart Rate Increase Equivalent to Transfusion

Abstract: Background Anemia is associated with morbidity and mortality and frequently leads to transfusion of erythrocytes. We sought to compare directly the effect of high inspired oxygen fraction vs. transfusion of erythrocytes on the anemia-induced increased heart rate (HR) in humans undergoing experimental acute isovolemic anemia. Methods We combined HR data from healthy subjects undergoing experimental isovolemic anemia in seven studies performed by our group. We examined HR changes associated with breathing 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…28,34,44,51,54,69 One main concern lies in whether a high resting heart rate is an independent predictor, because higher heart rates coexist with traditional risk factors of cardiovascular disease and poor health status. [10][11][12][13]70 Overall, the association of resting heart rate with risk of all-cause and cardiovascular mortality is independent of traditional risk factors of cardiovascular disease, suggesting that resting heart rate is a predictor of mortality in the general population. In addition, previous studies found that resting heart rate is also related to prognosis in settings of substantial cardiovascular comorbidities, such as renal disease, erectile dysfunction and pulmonary hypertension, as well as in noncardiovascular conditions such as chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…28,34,44,51,54,69 One main concern lies in whether a high resting heart rate is an independent predictor, because higher heart rates coexist with traditional risk factors of cardiovascular disease and poor health status. [10][11][12][13]70 Overall, the association of resting heart rate with risk of all-cause and cardiovascular mortality is independent of traditional risk factors of cardiovascular disease, suggesting that resting heart rate is a predictor of mortality in the general population. In addition, previous studies found that resting heart rate is also related to prognosis in settings of substantial cardiovascular comorbidities, such as renal disease, erectile dysfunction and pulmonary hypertension, as well as in noncardiovascular conditions such as chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…While the amount of oxygen dissolved in the blood is normally trivial compared with amount carried by hemoglobin, under conditions of severe anemia with a PaO 2 greater than 400 mm Hg, the amount of dissolved oxygen has been estimated to be equivalent to 3 g/dl of hemoglobin (11, 12). Oxygen delivery can also be increased by increasing cardiac output through use of inotropes or fluid administration.…”
Section: Methods Of Increasing Oxygen Deliverymentioning
confidence: 99%
“…In other words, these studies do not address the question of whether PRBC transfusion improves oxygenation and outcome in patients with severe anemia,(e.g., hemoglobin of 4 g/dL). However, it should be noted that Napolitano et al cite level 1 evidence that RBC transfusion is indicated in patients with hemorrhagic shock (12). Additionally while PRBC transfusion may not increase the VO 2 in circumstances where VO 2 /DO 2 dependency does not exist, transfusion can have other effects that may be beneficial in certain situations such as an increase in the FCD, changes in cardiac output, and an increased oxygen reserve.…”
Section: Impact Of Red Blood Cell Transfusion On Global Measures Of Omentioning
confidence: 99%
“…Belda, using a similar protocol, found the same result, but did not measure PwO 2 (16). These events reignited traditional disbelief that I had encountered when I showed that increasing arterial PO 2 could actually increase interstitial PO 2 without need for an increase in hemoglobin and also a reflexive and exaggerated fear of oxygen toxicity (90).…”
Section: * * * Thomas K Huntmentioning
confidence: 62%